2016
DOI: 10.1186/s40816-016-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of cytotoxicity, antihyperglycemic and antinociceptive activity of Polygonum hydropiper L. ethanolic leaf extract

Abstract: Background: Polygonum hydropiper L. is used by folk medicinal practitioners of Bangladesh. Juice of leaves is used in headache, pain, toothache, liver enlargement, gastric ulcer, dysentery, loss of appetite and dysmenorrhea; roots are used as stimulant; juice is applied to wounds, skin. In this study, we analyze the cytotoxicity property of aerial parts of the plant along with antihyperglycemic and antinociceptive activity. Methods: Cytoxicity was determined by brine shrimp lethality assay and antihyperglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Flavonoids are able to influence central nervous system activity (CNS) by binding to the benzodiazepine site on the GABA A receptor resulting in sedation, anxiolytic effects [11]. Several bioactive constituents have also been indicated from P. hydropiper with antihyperglycemic [12], antioxidant [13], antinociceptive [8], anti-inflammatory [14], cytotoxicity and anthelmintic activities [2].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are able to influence central nervous system activity (CNS) by binding to the benzodiazepine site on the GABA A receptor resulting in sedation, anxiolytic effects [11]. Several bioactive constituents have also been indicated from P. hydropiper with antihyperglycemic [12], antioxidant [13], antinociceptive [8], anti-inflammatory [14], cytotoxicity and anthelmintic activities [2].…”
Section: Introductionmentioning
confidence: 99%
“…Ethyl acetate extract showed a moderate dose-dependent effect, with writhing inhibition of 54.95% at a dose of 500 mg/kg compared with the standard aminopyrine (inhibition of 73.62% at dose of 50 mg/kg). Additionally, Oany et al [ 82 ] reported that crude EtOH extract of P. hydropiper leaves exhibited a good antinociceptive activity compared to the standard drug aspirin, displaying a reduction in the abdominal writhing’s number of 41.02% and 69.23%, respectively, at a dose of 400 mg/kg b.w. Petroleum ether and chloroform (Chl) extracts of P. barbata showed antinociceptive properties, with an inhibition of writhing response of 46.8% and 44.8%, respectively (at a dose of 400 mg/kg b.w.…”
Section: Pharmacological Activities Of Persicaria and Polygonum Products: Different Type Of Extractmentioning
confidence: 99%
“…Blood glucose levels were measured at intervals of 0 (fasting), 0.5, 1, 2, 3, 4 and 5 h by collecting blood samples from the tail vein (caudal vein). The percentage of change in blood glucose level was calculated by the following formula [23,24]:…”
Section: Anti-diabetic Activitymentioning
confidence: 99%